Amplified-Fragment Length Polymorphism Fingerprinting of Mycoplasma Species - Kokotovic, Branko (American Society for Microbiology, 1999)
Amplified-fragment length polymorphism (AFLP) is a whole-genome fingerprinting method based on selective amplification of restriction fragments. The potential of the method for the characterization of mycoplasmas was investigated in a total of 50 strains of human and animal origin, including Mycoplasma genitalium (n = 11), Mycoplasma pneumoniae (n = 5), Mycoplasma hominis (n = 5), Mycoplasma hyopneumoniae (n = 9), Myco plasma flocculare (n = 5), Mycoplasma hyosynoviae (n = 10), and Mycoplasma dispar (n = 5). AFLP templates were prepared by the digestion of mycoplasmal DNA with BglII and MfeI restriction endonucleases and subsequent ligation of corresponding site-specific adapters. The amplification of AFLP templates with a single set of nonselective primers resulted in reproducible fingerprints of approximately 60 to 80 fragments in the size range of 50 to 500 bp. The method was able to discriminate the analyzed strains at species and intraspecies levels as well. Each of the tested Mycoplasma species developed a banding pattern entirely different from those obtained from other species under analysis. Subtle intraspecies genomic differences were detected among strains of all of the Mycoplasma species analyzed. The extent of polymorphism varied markedly between the analyzed mycoplasmas, comprising pattern similarity levels from 61.7% detected among M. dispar strains to 95.9% detected among M. genitalium strains. The results of the present study provide evidence of the high discriminatory power of AFLP analysis, suggesting the possible applicability of this method to the molecular characterization of mycoplasmas.